2000
DOI: 10.1116/1.1319819
|View full text |Cite
|
Sign up to set email alerts
|

Control of the radio-frequency wave form at the chuck of an industrial oxide-etch reactor

Abstract: Radio frequency (rf) power is commonly applied to the chuck of a high-density plasma reactor in order to extract ions and to control the energy of the ions used for the fabrication of microelectronic devices. In many cases, the temporal shape of the rf wave form largely determines the shape of the spectrum of those extracted ions, thereby strongly affecting feature evolution. Using auxiliary rf circuits, we successfully made major changes to the rf-potential wave form at the chuck of an Applied Materials 5300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…In general, the RFEA measurements indicate how the IEDF can be controlled by driving a CCRF discharge with customized voltage waveforms, which is an important result for applications. 61,[88][89][90] By varying the phase the mean ion energy can be controlled. The mean value for the mean ion energy with two consecutive harmonics is 64 eV and can be varied by 35%, while the flux varies by 615 %.…”
Section: A Low Pressure (3 Pa)mentioning
confidence: 99%
“…In general, the RFEA measurements indicate how the IEDF can be controlled by driving a CCRF discharge with customized voltage waveforms, which is an important result for applications. 61,[88][89][90] By varying the phase the mean ion energy can be controlled. The mean value for the mean ion energy with two consecutive harmonics is 64 eV and can be varied by 35%, while the flux varies by 615 %.…”
Section: A Low Pressure (3 Pa)mentioning
confidence: 99%
“…Several authors have reported that the voltage amplitudes ðV n Þ of the n-th harmonic component at the electrode surface are influenced by the electrode reactance X n . 8,9) Kawata et al reported that the voltage amplitude observed at a high electrode impedance is higher than that observed at a low electrode impedance. 8) Berry et al reported that the maximum voltage amplitudes were obtained far from the highimpedance condition.…”
Section: Resultsmentioning
confidence: 98%
“…Extensive study has been carried out on the theoretical estimation and experimental observation of harmonic amplitude. [1][2][3][4][5][6][7][8][9][10][11] Harmonic amplitude is influenced not only by plasma parameters but also by the external circuit attached to the electrode. [6][7][8][9][10][11] It is commonly observed that a minor change in the circuit, such as changing the cable length, brings about large difference in the process result, owing to the change in the impedances of the external circuit at harmonic frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations